PENGARUH CAMPURAN ETANOL PADA PREMIUM TERHADAP EMISI GAS BUANG PADA SEPEDA MOTOR HONDA MEGAPRO 160 CC TAHUN 2007 - Miftahul F., Ahmad; Prasetyo, Imam; Towijaya, Towijaya (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2020)
One of the efforts to reduce exhaust emissions in vehicles is by adding addictive substances to premium fuels, one of the addictive substances in fuel mixing is ethanol. Ethanol is a high-octane fuel and can be used to increase the octane rating in fuel, which comes from sugary plants (sucrose) such as sugar cane, palm juice, coconut juice, etc., starchy plants (flour) cassava, sweet potato, sago, corn, etc. , and cellulose (legnocellulose) plants of wood, straw, and banana stems. Because the content of ethanol has many benefits, including increasing engine performance, saving fuel use, cleaning the combustion chamber, and being able to reduce exhaust emissions, this is because in the ethanol content there is oxygen which helps combustion in the combustion chamber more completely. This study aims to reduce the value of CO and HC concentrations and increase CO . emission levels2 on motorized vehicles. This test is carried out by adding the percentage of ethanol mixture that is 15%, 30%, 45% in premium fuel with engine speed variations of 2000, 2500, 3000, 3500, and 4000 rpm. the average decrease is significant from 2000-4000 engine speed, but the largest decrease occurred at 2000 rpm for the E30% of 2.15%, namely from 4.28% to 2.13%. While the concentration of HC emissions from 2000-4000 rpm decreased, the most decreased occurred at 4000 rpm for E30%, which was 270 ppm to 149 ppm.Keywords : ethanol, exhaust emissions